A RANDOMIZED CONTROLLED TRIAL OF THE EFFECTIVENESS OF THE FITT PRINCIPLE USING KNEE TUCK JUMP EXERCISES IN INCREASING LEG POWER - Wibisana, Muh Isna Nurdin; Pritama, Muhammad Atiq Noviudin; Zhannisa, Utvi Hinda (YLPK Mahardhika, 2024)
This research is based on the background of volleyball athletes master volleyball ball club when doing smash the jump is not optimal, as well as when blocking the opponent's smash range is higher than the blocking so it is easy to penetrate. This research was conducted with a quantitative approach with a preexperimental design method with a two-group pretest-posttest design. The sample in this study were 20 volleyball master volleyball ball club athletes. Treatment uses the principles of Frequency, Interval, Time and Type (FITT). Frequency is no more than 2x24 hours, intervals use the principle of submaximal intensity sets and reps, time uses duration based on the increase in heart rate beat per minute (bpm), type uses the aerobic glycolysis energy system. The results of the study were then processed using IBM SPSS 23. While the results of the knee tuck jump 93.10 became 99.00 paired sample T-test hypothesis test on pretest data and posttest data obtained sig value (2-tailed) = 0.002. Based on the results of the study, the application of knee tuck jump training has an effect on increasing leg power.